Restricted concentration models - Graphical Gaussian models with concentration parameters restricted to being equal - Højsgaard, S; Lauritzen, S (2005)
In this paper we introduce restricted concentration models (RCMs) as a class of graphical models for the multivariate Gaussian distribution in which some elements of the concentration matrix are restricted to being identical is introduced. An estimation algorithm for RCMs, which is guaranteed to converge to the maximum likelihood estimate, is presented. Model selection is briefly discussed and a practical example is given.